2016
DOI: 10.1016/j.plaphy.2016.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Salt acclimation processes in wheat

Abstract: Young wheat plants (Triticum aestivum L. cv. Mv Béres) were exposed to 0 or 25 mM NaCl for 11 days (salt acclimation). Thereafter the plants were irrigated with 500 mM NaCl for 5 days (salt stress). Irrigating the plants with a low concentration of NaCl successfully led to a reduction in chlorotic symptoms and in the impairment of the photosynthetic processes when the plants were exposed to subsequent high-dose salt treatment. After exposure to a high concentration of NaCl there was no difference in leaf Na co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 43 publications
5
33
0
Order By: Relevance
“…The total RNA content was isolated with a Direct-zol ™ RNA MiniPrep Kit (Zymo Research, USA) and TRI-Reagent (Zymo Research, USA) according to the manufacturer's instructions. M-MLV-Reverse transcriptase was used for the cDNA synthesis as described in [20]. …”
Section: Methodsmentioning
confidence: 99%
“…The total RNA content was isolated with a Direct-zol ™ RNA MiniPrep Kit (Zymo Research, USA) and TRI-Reagent (Zymo Research, USA) according to the manufacturer's instructions. M-MLV-Reverse transcriptase was used for the cDNA synthesis as described in [20]. …”
Section: Methodsmentioning
confidence: 99%
“…An initial response to salt stress is stomatal closure through the action of ABA (Garcia de la Garma et al 2015, Janda et al 2016). Enhanced ABA levels cause an increase in cytosolic Ca 2+ concentration, hence leading to guard cell depolarization and stomatal closure (Blatt 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Higher plants have developed several strategies to respond and adapt to salt stress and thus acquire stress tolerance, including activation of the antioxidant systems (Pandolfi et al 2016), induction of phytohormones (abscisic acid (ABA) and ethylene) (Garcia de la Garma et al 2015), control of the ion uptake and translocation, and adjustment of the photosynthetic processes (Janda et al 2014(Janda et al , 2016. A large body of evidence has shown that an early exposure to a moderate stressor can prepare the plants more quickly or actively to respond to subsequent stress (Bruce et al 2007, Li et al 2015, Liu et al 2017.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Higher plants, such as wheat (Triticum aestivum L.), have developed several survival mechanisms to improve their tolerance to salt stress (Janda et al 2016). High salt-resistant cultivars can maintain a better water status and reduce the effects of saltinduced osmotic stress by control of ion uptake by roots and their transport to photosynthetic tissues in leaves (Parida and Das 2005).…”
mentioning
confidence: 99%